Pendidikan Karakter Sebagai Pilar Generasi Berintegritas dalam Kurikulum Nasional - Najwa Syahada Gusna; Seni Ayu Ana Tasya; Cut Kumala Sari (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
In the midst of the development of information technology and globalization, character education is very important to form a young generation with integrity and noble character. This study aims to explore the role of character education in the national curriculum in Indonesia, as well as the challenges faced in its implementation. The method used is descriptive qualitative with literature study, collecting data from various related literature. The results of the study indicate that character education not only focuses on developing noble morals, but also functions as a pillar in creating a just and civilized society. Although there are supportive policies, challenges such as limited time, resources, and the phenomenon of 'disconnect' in the digital era are still obstacles. Therefore, it is necessary to integrate character education into all subjects and extracurricular activities, increase training for teachers, and collaboration between schools, families, and communities to create an environment that supports character formation. This study concludes that character education must be an integral part of a curriculum that is adaptive to changing times, with a relevant approach to teaching digital ethics and in-depth social skills.